Effectiveness and cost-effectiveness of an intensive and abbreviated individualized smoking cessation program delivered by pharmacists: A pragmatic, mixed-method, randomized trial. (November 2022) - Phillips, Leslie C.E.; Nguyen, Hai; Genge, Terri L.; Maddigan, W. Joy
Background: Tobacco use is the leading preventable cause of morbidity and mortality in Canada. Smoking cessation programs (SCPs) that are effective, cost-effective and widely available are needed to help smokers quit. Pharmacists are uniquely positioned to provide such services. This study compares the abstinence rates between 2 pharmacist-led SCPs and the cost-effectiveness between these and a comparator group. The study was conducted in St. John's, Newfoundland and Labrador. Methods: This pragmatic, mixed-method trial randomized smokers to either an existing intensive SCP or a new abbreviated SCP designed for community pharmacies. The primary outcome was 6-month abstinence rates. Cost-effectiveness was determined using abstinence rates for the SCPs and a comparator group. Incremental costs per additional quit were calculated for the trial duration, and incremental costs per life-year gained were estimated over a lifetime. Results: Quit rates for the SCPs were 36% (intensive) and 22% (abbreviated) ( p = 0.199). Incremental costs per life-year gained for the SCPs were $1576 (intensive) and $1836 (abbreviated). The incremental costs per additional quit, relative to the comparator group, for the SCPs were $1217 (intensive) and $1420 (abbreviated). Discussion: Both SCPs helped smokers quit, and quit rates exceeded those reported for a comparator group that included a general population of adult smokers (~7%). The incremental costs per additional quit for both SCPs compare favourably to those reported for other initiatives such as quit lines and hospital-based interventions. Conclusion: Pharmacist-led smoking cessation programs are effective and highly cost-effective. Widespread implementation, facilitated by remuneration, has potential to lower smoking prevalence and associated costs and harms.